Development of Engklek smart quiz based on education through art to improve learning outcome - Raihanah Sugiarto; Deasylina da Ary (Jurnal Prima Edukasia, 2026)
This study aims to develop the Engklek Smart Quiz learning medium based on Education Through Art and to determine its feasibility and effectiveness in improving the science learning outcomes of fourth-grade students on the topic of “Forces Around Us” at SD Negeri 1 Pendem. The method used is Research and Development (R&D) based on the ADDIE model. Data collection techniques included both tests and non-tests; tests were conducted via pre-tests and post-tests to measure improvements in student learning outcomes, while non-tests consisted of observations, interviews, questionnaires, and documentation. Data analysis utilized validity, reliability, and normality tests, paired t-tests, and N-Gain. The media was developed as a banner-based game integrating physical activities, art, “Do” and “Ask” question cards, floor patterns, and music barcodes. The validation results indicate that the teaching material is highly suitable, with an 89% approval rate from subject matter experts and a 96% approval rate from media experts. The material is also considered highly practical, based on a 92.65% approval rate from teachers and a 94.20% approval rate from students. The effectiveness test showed a significant improvement in learning outcomes with a significance level of <0.05. The N-Gain values of 0.5634 for the small group and 0.6083 for the large group fall into the moderate category. Thus, this medium is considered appropriate, practical, and effective for IPAS learning, and the use of game- and art-based learning media can serve as an effective alternative learning strategy in creating active, creative, and enjoyable learning experiences for elementary school students.